Katharsis of the skin: peeling applications and agents of chemical peelings in Greek medical textbooks of Graeco‐Roman antiquity. (17th July 2018) - Ursin, F.; Steger, F.; Borelli, C.
Abstract: Background: Recipes for peelings date back to medical texts of old Egypt. The oldest medical papyri contain recipes for 'improving beauty of the skin' and 'removing wrinkles' by use of agents such as salt and soda. The Egyptian Queen Cleopatra (69–30 BC) is said to have taken bathes in donkey's milk to improve the beauty of her skin. However, little is known about other agents and peeling applications in later Greek medical textbooks. Objective: We will discover new agents and describe ancient peeling applications. First, we will have to identify ancient Greek medical terms for the modern terms 'peeling' and 'chemical peeling'. Second, on the basis of the identified terms, we will perform a systematic full‐text search for agents in original sources. Third, we will categorize the results into three peeling applications: (i) cleansing, (ii) aesthetical improvement of the skin and (iii) therapy of dermatological diseases. Methods: We performed a full systematic keyword search with the identified Greek terms in databases of ancient Greek texts. Our keywords for peeling and chemical peeling are 'smēxis' and 'trīpsis'. Our keywords for agents of peeling and chemical peeling are 'smégmata', 'rhýmmata', 'kathartiká' and 'trímmata'. Results: Diocles (4th century BC) was the first one who mentioned 'smēxis' and 'trīpsis' as parts of daily cleansing routine. Criton (2nd century AD) wrote about peeling applications, but any reference to the agents is lost. Antyllus (2nd century AD) composed three lists of peeling applications including their agents. Conclusion: Greek medical textbooks of Graeco‐Roman antiquity report several peeling applications such as cleansing, brightening, darkening, softening and aesthetical improvement of the skin by use of peeling and chemical peeling, as well as therapy of dermatological diseases. There are 27 ancient agents for what is contemporarily called peeling and chemical peeling. We discovered more specific agents than hitherto known to research.